2010
DOI: 10.1088/1367-2630/12/2/025011
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic bound entanglement in thermal graph states

Abstract: We address the presence of bound entanglement in strongly-interacting spin systems at thermal equilibrium. In particular, we consider thermal graph states composed of an arbitrary number of particles. We show that for a certain range of temperatures no entanglement can be extracted by means of local operations and classical communication, even though the system is still entangled. This is found by harnessing the independence of the entanglement in some bipartitions of such states with the system's size. Specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…On the other hand, for some models, it has already been shown that there is still entanglement present in these models. This was first demonstrated for GHZ Hamiltonians [4], but has since been shown to exist in simpler models, such as for square lattices [5].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, for some models, it has already been shown that there is still entanglement present in these models. This was first demonstrated for GHZ Hamiltonians [4], but has since been shown to exist in simpler models, such as for square lattices [5].…”
Section: Introductionmentioning
confidence: 92%
“…Due to the numerical work of [5], we already expect that the critical temperature will not be significantly affected. In the case of a 1D chain, we can derive a recursion relation for the polynomial,…”
Section: Stability To Perturbationsmentioning
confidence: 99%
“…We demonstrate that in such a setup bound entangled states are produced for certain choices of temperature and coupling. The presence of undistillable entanglement in thermal finite-dimensional systems has been considered in [49].…”
Section: Multipartite Bound Entanglementmentioning
confidence: 99%
“…Since system excitations are created by the Z Pauli operators, the thermal state is equivalent to the ground state under independent dephasing [13,17,18]. That is,…”
Section: Introductionmentioning
confidence: 99%
“…This difference comes from the fact that state (8) is not symmetric with respect to the exchange of qubits. At this point, the system becomes bound entangled [18]. If N Ap|BsBp = 0 = N Bp|ApBs , no entanglement can be extracted from the bipartitions A p |B s B p or B p |A p B s by local operations assisted by classical communication (LOCCs).…”
Section: Introductionmentioning
confidence: 99%